2007
DOI: 10.1556/avet.55.2007.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the molecular effects of the mycotoxins β-zearalenol and deoxynivalenol in porcine endometrial cells — A review

Abstract: The mycotoxins β-zearalenol (β-ZOL) and deoxynivalenol (DON) produce toxic effects that result in diseases in humans and animals. The molecular mechanisms that control the mycotoxin-mediated effects are far from being completely understood. Various results show that these mycotoxins could inhibit cell proliferation. In the present short communication, the influence of β-ZOL and DON on the abundance and phosphorylation state of kinases that are included in regulation of the initiation of mRNA translation (which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated that DON could decrease cell proliferation and reduce the viability of different cells with different concentrations. 12,25 In addition, DON can significantly inhibit the proliferation of IPEC-J2 cells. 11,19,26,27 In our study, the cell viability assay showed a similar suppressive response to 200 ng mL −1 of DON and 2000 ng mL −1 of DON at 24 h, 48 h, and 72 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that DON could decrease cell proliferation and reduce the viability of different cells with different concentrations. 12,25 In addition, DON can significantly inhibit the proliferation of IPEC-J2 cells. 11,19,26,27 In our study, the cell viability assay showed a similar suppressive response to 200 ng mL −1 of DON and 2000 ng mL −1 of DON at 24 h, 48 h, and 72 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Deoxynivalenol affects animal and human health causing acute temporary nausea, vomiting, diarrhea, abdominal pain, headache, dizziness, and fever (Sobrova et al, 2010). At the molecular level, deoxynivalenol disrupts normal cell function by inhibiting protein synthesis via binding to the ribosome and by activating critical cellular kinases involved in signal transduction related to proliferation, differentiation and apoptosis (Wollenhaupt et al, 2007;Abdel-Twab et al, 2009). Relative to toxicity, there are marked species differences, with the pig being most sensitive to deoxynivalenol, followed by rodent > dog > cat > poultry > ruminants (Rotter et al, 1996).…”
Section: Introductionmentioning
confidence: 99%